Aftermarket Volatility and Underpricing of Initial Public Offerings in the Stock Exchange of Thailand (SET) and the Market of Alternative Investment (MAI) - Kitkanasiri, Chavalit; Pan-urai, Jarukorn; Kiatkamonrat, Piyawat (Journal of Applied Economics and Management Strategy, 2023)
This research investigates the relationship between the level of underpricing of the Initial Public Offerings (IPO) listed on the Stock Exchange of Thailand (SET) and the Market of Alternative Investment (MAI) in Thailand during the period of January 2011 to July 2021. We found a strong positive relationship between the level of underpricing and both overall volatility and firm-specific risk. However, we did not find a clear relationship between the level of underpricing and systematic risk in these two markets. Furthermore, market timing, capital structure, and industry factor did not play an important role in determining the level of underpricing in the both markets. Last but not least, we found that the level of underpricing and the overall volatility in the Stock Exchange of Thailand (SET) are statistically lower than those in the Market of Alternative Investment (MAI) in Thailand. This reflects the higher level of information asymmetry in the Market of Alternative Investment (MAI) than in the Stock Exchange of Thailand (SET).